Strategic Model for Mangrove Forest Resource Management in Boalemo District, Gorontalo Province - Melo, Ramla Hartini; Niode, Alim S.; Pambudi, Moch. Rio; Laya, Nibras K.; Pratama, M. Iqbal Liayong; Masruroh, Masruroh; Ninasafitri, Ninasafitri (Jambura Geoscience Review, 2024)
Mangrove forest destruction in Boalemo Regency has increased significantly over the past decade. The condition of mangrove forests has been degraded due to the pressure of population growth, especially in coastal areas.  Damage to mangrove forest resources is certainly very dangerous to the ecosystem of fisheries resources, biodiversity and destroys the stability of coastal forests that support the protection of inland and rural agricultural crops. The purpose of this research is to design a model of sustainable mangrove forest resource management strategy in Boalemo District, Gorontalo Province, so that it can be applied as a policy in improving and optimizing mangrove forest resource management efforts in Gorontalo Province. The method used is Interpretive Structural Modeling (ISM). The results showed that there are thirteen sub-elements of program requirements needed to build the model, of the thirteen elements of program requirements there are no sub-elements that occupy quadrant I, in quadrant II there are two sub-elements and in quadrant III there are six sub-elements, in quadrant IV is occupied by five sub-elements which are key elements to build a mangrove forest resource management strategy model.